2016
DOI: 10.1051/sicotj/2016035
|View full text |Cite
|
Sign up to set email alerts
|

A suture technique for easier reduction and repair of bucket-handle meniscal tears while using the all-inside devices

Abstract: Arthroscopic repair of bucket-handle meniscal tears is difficult due to their complex pathology. Many meniscal repair techniques such as all-inside, inside-out, and outside-in have been described for the treatment of these tears. Loss of reduction is a likely complication with the use of new-generation, all-inside suture instruments, as the tip of the needle is extracted following advancement of the first implant behind the capsule. The complication may be encountered quite often and renders the use of the men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…However, recent studies suggest that good and even excellent results are obtained for chronic lesions [17,18]. Reducing the BHMMT and reducing it in place during the repair process are challenging but essential steps for successfully repairing this type of injury [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies suggest that good and even excellent results are obtained for chronic lesions [17,18]. Reducing the BHMMT and reducing it in place during the repair process are challenging but essential steps for successfully repairing this type of injury [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…We used a combined inside-out and all-inside modality with multiple suturing techniques to ensure stable and adequate fixation. This approach was approved as being appropriate by many researchers 1,2,[12][13][14][15] ; however, some authors have recorded better outcomes with all-inside repairs when compared with inside-out repairs. 12 Our assertion was similar to those of Yilmaz et al, 13 who found out that combined CHRONIC ISOLATED BUCKET-HANDLE MENISCAL TEAR e5 inside-out and all-inside meniscal repair technique is a successful and cost-effective treatment method in bucket-handle meniscus tears.…”
Section: Discussionmentioning
confidence: 99%
“…By placing the reduction suture, a clear view of the posterior meniscus is obtained to facilitate repair. Other techniques 13,14,19,20 had been described to reduce the tear. The current technique reduces the torn segment with an all-inside repair.…”
Section: Discussionmentioning
confidence: 99%